Material and geometrical characteristics of structural steels based on statistical analysis of metallurgical products - Kala, Zdeněk; Melcher, Jindřich; Puklický, Libor (Journal of Civil Engineering and Management, 2009)
The experimental research results of material and geometrical characteristics of Czech steel are given in the presented paper. Measurements are carried out for the yield strength of plates made of steel grade S355. The values measured are used to compute axial resistances which are compared with the resistance resulting from standard (nominal) values. In this paper, there was used a statistical information for evaluating the results of strength measurements on a series of plates and hot‐rolled profiles under tension to determine the adequate partial γM0 safety factor. Santrauka Straipsnyje pateikti Čekijos plienų mechaninių ir geometrinių charakteristikų eksperimentinių tyrimų rezultatai. Atlikti S355 klasės plieno plokštės takumo stiprio matavimai. Nustatytos reikšmės naudojamos ašiniam stipriui apskaičiuoti, o gauti rezultatai palyginti su standartinėmis (nominaliosiomis) vertėmis. Plieno plokščių ir karštai valcuotų profilių tempiamojo stiprio matavimo rezultatams įvertinti pasitelkta statistinė informacija. Įvertintas dalinio patikimumo koeficiento γM0 adekvatumas. First Published Online: 14 Oct 2010 Reikšminiai žodžiai: medžiaga, plienas, takumo stipris, patikimumas, konstrukcija, projektavimas, atsitiktinis dydis.